2018
DOI: 10.1111/gcb.14027
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the long‐term effects of disturbance on soil biogeochemistry in a wet tropical forest ecosystem

Abstract: Climate change is increasing the intensity of severe tropical storms and cyclones (also referred to as hurricanes or typhoons), with major implications for tropical forest structure and function. These changes in disturbance regime are likely to play an important role in regulating ecosystem carbon (C) and nutrient dynamics in tropical and subtropical forests. Canopy opening and debris deposition resulting from severe storms have complex and interacting effects on ecosystem biogeochemistry. Disentangling these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 65 publications
0
28
0
Order By: Relevance
“…Chev., and Prestoea acuminata (Wildenow) H.E. Moore (=Prestoea montana (Graham) A. Henderson and G. Galeano) [31]. Mean air temperature was 24 °C [31], and mean annual precipitation was 3500 mm [32].…”
Section: Study Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chev., and Prestoea acuminata (Wildenow) H.E. Moore (=Prestoea montana (Graham) A. Henderson and G. Galeano) [31]. Mean air temperature was 24 °C [31], and mean annual precipitation was 3500 mm [32].…”
Section: Study Sitesmentioning
confidence: 99%
“…Moore (=Prestoea montana (Graham) A. Henderson and G. Galeano) [31]. Mean air temperature was 24 °C [31], and mean annual precipitation was 3500 mm [32]. Although this is a non-seasonal forest, there is typically a weak dry season from December to March [14].…”
Section: Study Sitesmentioning
confidence: 99%
“…They also showed there was an elevation of the soil microbial biomass that lasted from week 1 until at least 120 weeks after deposition of the canopy material. The hurricaneinduced deposition of course woody debris (CWD) from the canopy caused an increased immobilization of the nutrients, resulting in a decreased availability of these for the food web [11] [18] [19] [17] [20], a slowing down decomposition activities in the forest soils [9].…”
Section: Introductionmentioning
confidence: 99%
“…There have been experimental studies that have shown the deposition of canopy material to the tropical forest floor, in a manner simulating the effects of a hurricane, result in nutrient pulses of more labile forms of C, N and phosphorus derived from the younger leaf litter from the canopy for about the first two years[4] [10] [14] [15] [16] [17]. This material is quickly processed within the first year [7] [11] [19], and is followed by utilization of the CWD deposited on the forest floor, resulting in a slower rate of processing activities [9] [11] [17] [18] [19][20].All these processes would be associated with the types of increases in inorganic N and Biomass C, and changes in the microbial communities that we observed in the forest soils after the…”
mentioning
confidence: 99%
“…Several studies have characterized the P dynamics and distributions through either chemical sequential extraction or 31 P-NMR spectroscopy in tropical forests [24][25][26], subtropical forests [27,28], and temperate forests [4,23]. Negassa and Leinweber [29] indicated that only a few studies have characterized P in soils by comparing 31 P-NMR and sequential chemical extraction.…”
Section: Introductionmentioning
confidence: 99%